Clinical and Humanistic Outcomes of Pharmaceutical Care Interventions in Diabetes Mellitus: A Systematic Review and Meta-Analysis. (2019)
Background: Diabetes mellitus is a chronic disease for which life-long medications and care are needed. Effectiveness of care is related to good glycemic control, which is desired to forestall complications. Objective: This study evaluated the effectiveness of pharmaceutical care (PC) services provided by pharmacists in improving clinical and humanistic outcomes in diabetes mellitus patients. Method: Five databases (PubMed/Medline, Embase, Scopus, Cochrane Central Register of Control Trials and Google Scholar) were systematically searched for randomized controlled trials (RCTs) reported in English using free text and medical subject headings keywords. Studies which had PC intervention arm, a control group, type1 and type 2 diabetes mellitus patients; clinical and/or humanistic outcomes were included. For metaanalysis, standard mean difference evaluated with random effect model at P<0.05 was reported. Significant heterogeneity was further evaluated with sensitivity and subgroup analyses. Results: A total of 41 RCTs with 7,448 patients were eligible out of 1222 citations. PC intervention significantly lowered glycosylated hemoglobin, fasting blood glucose, systolic blood pressure, diastolic blood pressure, total cholesterol, and low density lipoprotein cholesterol (P < 0.05), with significant heterogeneity. PC intervention also improved self-care but medication adherence, disease knowledge and quality of life were not improved. PC services offered (patient education, identification and resolution of drug therapy problems, and pharmacotherapy evaluation) were not uniform across the studies. Conclusion: The review and meta-analysis showed that PC intervention is of great benefit to improve most clinical outcomes which may result in better disease management. A call is however made for standardized pharmaceutical care intervention.